Venture capital and private equity : a case book - Lerner, Joshua (New York : John Wiley and Sons, 2000)
Raising and structuring private equity funds. Private equity investments. Exiting private equity investmens. Transplanting the private equity model...
Keywords: Economics; United States; Venture capital; Venture capital -- United States -- Case studies; Capital investments -- United States -- Case studies